Sorrel : in the shadow of the bear - Randall, David, 1972- (Sydney : Hachette Livre Australia, 2007)
The third and final book in the epic fantasy series for young people 'In the Shadow of the Bear' featuring courageous Clovermead Wickward.
For children aged 11+.
Previously published: New York : Margaret K. McElderry Books, 2006.